VALORES NUTRICIONAIS E QUALITATIVOS DE CARNES BOVINAS (LONGISSIMUS THORACIS) PROVENIENTES DE SISTEMAS DE PRODUÇÃO ORGÂNICA E CONVENCIONAL - Ana Paula Costa Rodrigues Ferraz; Jessica Moraes Malheiros; Renata Maria Galvão de Campos Cintra; Luis Artur Loyola Chardulo (Universidade do Estado do Rio de Janeiro, 2015)
This study aimed to evaluate the effects of livestock production in organic and conventional management system in relation to the meat quality of Nellore male cattle (Bos indicus). Eight animals raised  organically  and 15 animals produced under conventional system finished in feedlot for 90 days were used. After slaughter, the carcasses were cooled within 24 to 48 hours, and two samples of the Longissimus thoracis were collected with approximately 2.54 cm thick between the 12th to 13th ribs of the left half of each animal. Chemical characteristics were evaluated, such as total lipids (TL) and myofibrillar fragmentation index (MFI). Additionally,   characteristics such as shear force (SF), rib eye area (REA), marbling index (MI), backfat thickness (BFT), centesimal composition, total losses (LT) and instrumental coloring were evaluated. The organic  samples showed best results for instrumental color, the most important  item considered at the time of purchase. The average shear force was lower for organic meat and is positively related with  tenderness. Significant differences between the two groups can also be observed in the total lipid analysis, fat thickness and moisture content, which showed higher values than in the animals finished in feedlot. DOI: http://dx.doi.org/10.12957/demetra.2015.14293